Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine the inverse of the function \( f(x) = 2x + 1 \), we need to follow a systematic process. Let's go through the steps in detail:
1. Write the function in terms of \( y \):
[tex]\[ y = 2x + 1 \][/tex]
2. Swap \( x \) and \( y \):
To find the inverse, we swap \( x \) and \( y \):
[tex]\[ x = 2y + 1 \][/tex]
3. Solve for \( y \):
Now, we need to solve this equation for \( y \). Start by isolating \( y \):
[tex]\[ x - 1 = 2y \][/tex]
[tex]\[ y = \frac{x - 1}{2} \][/tex]
4. Simplify the expression:
The equation can be rewritten as:
[tex]\[ y = \frac{1}{2}x - \frac{1}{2} \][/tex]
5. Express the inverse function:
The inverse function \( f^{-1}(x) \) is then:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
Now we compare this result with the given options:
1. \( h(x) = \frac{1}{2}x - \frac{1}{2} \)
2. \( h(x) = \frac{1}{2}x + \frac{1}{2} \)
3. \( h(x) = \frac{1}{2}x - 2 \)
4. \( h(x) = \frac{1}{2}x + 2 \)
Clearly, the first option \( h(x) = \frac{1}{2}x - \frac{1}{2} \) matches our derived inverse function.
Thus, the inverse function is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
So, the correct answer is the first option:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
1. Write the function in terms of \( y \):
[tex]\[ y = 2x + 1 \][/tex]
2. Swap \( x \) and \( y \):
To find the inverse, we swap \( x \) and \( y \):
[tex]\[ x = 2y + 1 \][/tex]
3. Solve for \( y \):
Now, we need to solve this equation for \( y \). Start by isolating \( y \):
[tex]\[ x - 1 = 2y \][/tex]
[tex]\[ y = \frac{x - 1}{2} \][/tex]
4. Simplify the expression:
The equation can be rewritten as:
[tex]\[ y = \frac{1}{2}x - \frac{1}{2} \][/tex]
5. Express the inverse function:
The inverse function \( f^{-1}(x) \) is then:
[tex]\[ f^{-1}(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
Now we compare this result with the given options:
1. \( h(x) = \frac{1}{2}x - \frac{1}{2} \)
2. \( h(x) = \frac{1}{2}x + \frac{1}{2} \)
3. \( h(x) = \frac{1}{2}x - 2 \)
4. \( h(x) = \frac{1}{2}x + 2 \)
Clearly, the first option \( h(x) = \frac{1}{2}x - \frac{1}{2} \) matches our derived inverse function.
Thus, the inverse function is:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
So, the correct answer is the first option:
[tex]\[ h(x) = \frac{1}{2}x - \frac{1}{2} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.